Efficacy of soft palatal augmentation prosthesis for oral functional rehabilitation in patients with dysarthria and dysphagia: a protocol for a randomised controlled trial - Naoki Kodama; Tomonori Yokoyama; Takao Mukai; Kana Takao; Takashi Hiraoka; Nobuyuki Arai; Jitsuro Yano; Hiroaki Nagatsuka; Yousuke Manda; Kozo Hanayama; Shogo Minagi (BMJ Open)
Introduction Palatal augmentation prosthesis (PAP) is used in patients with articulation and swallowing disorders caused by postoperative loss of tongue tissue due to tongue cancer, cerebrovascular disease sequelae and age-related hypofunction. We have previously reported a newly designed soft PAP fabricated using an thermoplastic material that is particularly appropriate for early intervention. However, the effect of soft PAP on oral function improvement remains to be elucidated. The aim of this study is to investigate whether soft PAP can improve dysarthria and dysphagia occurring as cerebrovascular disease sequelae.Methods and analysis This prospective, randomised, controlled trial will compare the immediate and training effects of rehabilitation using soft PAP with those of rehabilitation without using it. Primary outcomes are the single-word intelligibility test score and pharyngeal transit time (PTT). Secondary outcomes are tongue function (evaluated based on maximum tongue pressure, repetitions of tongue pressure and endurance of tongue pressure), articulation function (evaluated based on speech intelligibility, oral diadochokinesis, Voice-Related Quality of Life (V-RQOL)) and swallowing function (evaluated using Eating Assessment Tool-10). The study results will help determine the efficacy of Soft PAP in improving functional outcomes of word intelligibility and PTT. We hypothesised that early rehabilitation using Soft PAP would more effectively improve articulation and swallowing function compared with conventional rehabilitation without using soft PAP.Ethics and dissemination Ethical approval was obtained from the Okayama University Certified Review Board. The study findings will be published in an open access, peer-reviewed journal and presented at relevant conferences and research meetings.Trial registration number jRCTs062200054.